Development and validation of knowledge and attitude questionnaire on intellectually disabled adolescents' health issues and accessibility to primary healthcare services among primary healthcare providers - Ismail, Nur Akmal (2024)
Background: Adolescents who have intellectual disabilities face distinct health challenges that necessitate specialized care and understanding. Accessing primary healthcare services poses further challenges for this population. The objectives of this study were to explore intellectually disabled adolescents’ health issues and their accessibility to primary healthcare services and subsequently develop a new questionnaire to assess primary healthcare providers' knowledge and attitudes regarding those concerns. Methodology: The study was conducted in two phases using a mixed-method approach. The first phase involved a questionnaire development based on an extensive literature review, in-depth interviews, content validation, face validation, and pretesting. In-depth interviews were conducted among 26 respondents including 12 caregivers, 10 primary healthcare providers who had experience in managing intellectually disabled adolescents, and four health and medical experts in the management of intellectual disabilities. They were selected using purposive sampling method. Data were analyzed using thematic analysis. The qualitative study findings informed item generation. The content validation was performed among seven experts and face validation was conducted among 10 primary healthcare providers in Kelantan. The second phase involved item response theory (IRT), exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to measure the questionnaire’s internal structure validity and reliability. A cross-sectional study was conducted among 444 primary healthcare providers to assess IRT, EFA and CFA. A multistage sampling was used to select the healthcare providers from 20 government primary health clinics in Kelantan. Result: The qualitative findings identified intellectually disabled adolescents’ health issues such as medical conditions, mental health conditions, developmental disabilities, high-risk behaviours, nutrition-related problems, as well as sexual and reproductive health issues. The findings also identified their challenges in accessing primary healthcare services according to Levesque’s model namely, approachability, acceptability, availability, affordability and appropriateness. The findings from qualitative study and literature reviews were integrated into the development of new knowledge and attitude questionnaire. An initial questionnaire was developed with 59 knowledge items and 61 attitude items within nine domains. Following the content validation, face validation, IRT for knowledge section and EFA as well as CFA for attitude section, the final questionnaire has resulted in 14 general information items, 38 knowledge items, and 28 attitude items within the same nine domains. Conclusion: A new Malay-validated questionnaire demonstrated strong reliability and valid psychometrics for assessing primary healthcare providers’ knowledge on health issues of intellectually disabled adolescents and their attitudes towards these adolescents’ accessibility to primary healthcare services.